Glycated proteome: from reaction to intervention - Kulkarni, Mahesh J.; Korwar, Arvind M.; Mary, Sheon; Bhonsle, Hemangi S.; Giri, Ashok P. (Proteomics Clinical Applications, 2013)
Glycation, a nonenzymatic reaction between reducing sugars and proteins, is a proteome wide phenomenon, predominantly observed in diabetes due to hyperglycemia. Glycated proteome of plasma, kidney, lens, and brain are implicated in the pathogenesis of various diseases, including diabetic complications, neurodegenerative diseases, cancer, and aging. This review discusses the strategies to characterize protein glycation, its functional implications in different diseases, and intervention strategies to protect the deleterious effects of protein glycation.
Keywords: aging; Diabetes; Glycation; RAGE